Alfred Gras Oral History Interview, 2005 - Gras, Alfred (2005)
This oral history interview was conducted with Dr. Alfred Gras on September 23, 2005 by Jessica Roseberry. Gras discusses his renaissance of interest in his own receipt of penicillin as medical student; notes from his father's journal about the event; Mary Poston; David Tillerson Smith; sulfonamides; his near death and miraculous recovery from bilateral staphylococcal pneumonia from use of penicillin; availability of penicillin at the time; Dr. Edward Levy and Dr. John Peck setting up penicillin drip; Dr. Levy and Dr. Peck telling him he was receiving a "vitabrew " in his leg; vein problems due to the treatment; further use of the penicillin extracted from his urine; obtaining the penicillin; his lack of having heard about penicillin; write-up of case in New England Journal of Medicine; cost (none) of his experimental penicillin versus estimated cost of same amount ($10,000); coming to Duke Medical School; lack of event status of the incident among his peers; cessation of penicillin due to complications from intravenous delivery; and further career.